Draʿ Abu el-Naga, Ägypten: Die spätantike koptische Klosteranlage Deir el-Bachît - Burkard, Günter (e-Forschungsberichte des DAI, 2023)
Deir el-Bakhit is a Coptic monastery, actually the ancient monastery of Paulos, situated on the hill of Dra‘ Abu el-Naga. The site offers a unique chance to follow Christian settlement in the ancient pharaonic necropolis from anachoretic beginnings in the later 5th century to monastic structures from the early 7th century until its end in the early 10th century. Research concentrates on the monastery building itself, its workshops and cemetery, no less, however on the system of ways and road posts and external installations which reveal a rich picture of the site which served as a way station at the beginning of the desert road to the oases. Important texts, ostraca and graffiti, were found which shed light on the people who lived in the monastery and on its functions.